PERFIL EPIDEMIOLÓGICO DE UMA UNIDADE DE TERAPIA INTENSIVA NEONATAL EM GOIÁS, BRASIL ENTRE 2009 E 2013 - Filipe Rodrigues de Sousa Borges; Danyelle Rocha da Silva; Mariana Akemi Matsuy; Mirian Paiva Silva; Karla Cristina Naves de Carvalho (UniEVANGÉLICA, 2016)
Objective: To describe the epidemiological profile of a neonatal intensive care unit in a public hospital in Anápolis, Goiás between 2009 and 2013. Methods: Epidemiological study, observational, descriptive, retrospective, with quali-quantitative approach. Data were collected from medical records of newborns admitted to the unit during that period and analyzed using the chi-square test. Results: There was a predominance of males (54.4%), cesarean section (54.6%) newborns at term (48.5%) and normal weight (50.9%). The mortality rate was 6.1%. The most prevalent diseases were respiratory distress syndrome, prematurity and jaundice. There was no statistically significant difference in relation to weight and gender of newborns with respiratory distress (p = 0.007), prematurity (p = 0.012) as well as the type of birth in premature newborns (p<0.000) Conclusions: The epidemiological profile is to support essential primary prevention therefore relate to two factors: an improved prenatal and continuing education of health professionals.